Luxury and Technology: an phenomenological analysis of the Louis Vuitton designer handbags Canvas of the Future (ModaPalavra e-periódico, 2020)
To broaden their cultural influence, gain new consumers orretain current loyalty (target), luxury brand managers alsodiversify products and marketing strategies. An example ofthis is the launch of the Canvas of the Future bag, a LouisVuitton brand product that boasts digital technologycapabilities, integrating the idea oftechnological innovationwith luxury brand and product concepts. Thus, we sought todescribe and interpret the perception of Fashion experts aboutthe product, conducting a descriptive-qualitative research,whose epistemological basis is Phenomenology. In summary,four research steps were considered and developed to: 1)explore; 2) collect; 3) relate information, and 4) raisepropositions. Among the results of the study, we highlightconsiderations such as: pioneering, innovative, surreal andfuturistic regarding the product, confirming the contemporaryhybridism between the tradition of fashion and technologicalinnovation, highlighting the revision and repositioning of thebrand andthe product of Lux.
Keywords: luxury product.; digital technology; fashion phenomenology.